2010
DOI: 10.4161/cc.9.13.12148
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the PI3K-like protein kinase members ATM and DNA-PKcs at DNA double strand breaks

Abstract: T he protein kinases ATM and DNA-PKcs play critical roles in the cellular response to DNA double strand breaks (DSBs). ATM and DNA-PKcs are activated in response to DSBs and play several important roles in propagation of the damage signal and for the repair of DNA damage. Recent work from several groups, including ours, has focused on studying the dynamics of each of these proteins at DSBs and the requirements and factors which play a role(s) in this process. The use of live cell imaging of fluorescently-tagge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 54 publications
(82 reference statements)
6
34
0
Order By: Relevance
“…You et al (2005) suggested a mechanism where MRN complexes in the vicinity of DNA DSB support signal amplification (i.e., phosphorylation of ATM substrates) by successive recruitment, activation and release of ATM kinase, where the release rate of active ATM could be influenced by autophosphorylation. Data on the dynamics of multiple ATM autophosphorylation sites [54] and behavior of active forms of ATM kinase on chromatin breaks support this idea [55]. Interestingly, Tel2 (hCLK2), a regulator of ATM stability also binds to the HEAT repeat area in ATM (aa 830-1290) as well as the C-terminus of ATM (2,680-3,056) [30].…”
Section: Role Of the N-terminusmentioning
confidence: 51%
“…You et al (2005) suggested a mechanism where MRN complexes in the vicinity of DNA DSB support signal amplification (i.e., phosphorylation of ATM substrates) by successive recruitment, activation and release of ATM kinase, where the release rate of active ATM could be influenced by autophosphorylation. Data on the dynamics of multiple ATM autophosphorylation sites [54] and behavior of active forms of ATM kinase on chromatin breaks support this idea [55]. Interestingly, Tel2 (hCLK2), a regulator of ATM stability also binds to the HEAT repeat area in ATM (aa 830-1290) as well as the C-terminus of ATM (2,680-3,056) [30].…”
Section: Role Of the N-terminusmentioning
confidence: 51%
“…Considering a potential role in limiting DSB persistence, blocking the kinase activity of DNA-PKcs could decrease the rate of EJ, thereby increasing the probability that multiple DSBs persist simultaneously, which could lead to an elevated frequency of distal end use. Regarding this possibility, blocking autophosphorylation of DNA-PKcs has been shown to cause its persistent retention at DSBs, as well as delayed DSB repair (58,59). Such autophosphorylation may be important to release DNA-PKcs during later steps of EJ, because a blocked synaptic complex could delay ligation (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…As is suggested by PF-05212384 post-IR treatment γH2AX data, radiation modulation is at least in part secondary to mitigation of key components of the DNA-DSB repair pathway. ATM and DNA-PKc protein kinases belong to the PI3K-like kinase (PIKK) family, along with PI3K, mTORC1, and mTORC2 (2123). Given the considerable homology between the catalytic sites of the previously listed protein kinases we performed immunoblots investigating ATM and DNA-PKc activation following IR with and without PF-05212384 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, Burma et al have eloquently demonstrated that the radiosensitizing effect propagated by NVP-BEZ-235 is in part secondary to catalytic inhibition of the ATM and DNA-PKc enzymes (21, 22). The ATM and DNA-PKc protein kinases are critical components of the DNA-DSB repair response and belong to the PI3K-like kinase (PIKK) family, along with PI3K, mTORC1, and mTORC2 (23, 24). DNA repair enzyme inhibition radiosensitization may be a viable approach in select anatomic sites, but normal tissue radiosensitization will likely limit this approach clinically for the vast majority of malignancies (25).…”
Section: Introductionmentioning
confidence: 99%